Knowledge, Attitude and Practice at AI in Education: Student’s Perception - Bhattarai, Pragya; Nepal, Prashant; Khatri, Pravin; Dhungana, Prinja; Adhikari, Ranjit; Thapa Magar, Rashmi; Chand, Keshab (NPRC Journal of Multidisciplinary Research, 2024)
As AI becomes a bigger part of our schools and universities, it’s important to get a handle on how students feel about it, what they know, and how they use it. In this study, we combined surveys and interviews to dig into these areas. We asked students about their thoughts on AI, their understanding of how it works, and their experiences using AI tools in their classes. The interviews helped us understand their responses in more depth. We found that students are generally excited about AI and its potential to make learning more personalized. However, there’s a gap between their enthusiasm and their actual understanding of AI technology and its uses. This gap makes it harder for them to use AI tools effectively. Our study highlights the need for better AI education to help students bridge this gap. Schools should focus on improving students’ AI knowledge and skills. By doing so, they can better align AI tools with students’ needs and enhance their learning experiences. This research gives us valuable insights into how students’ attitudes and knowledge about AI impact their use of these tools, helping shape more effective educational strategies.